Robust uncalibrated visual stabilization for nonholonomic mobile robots. (18th March 2020) - Huang, Yao; Su, Jianbo
ABSTRACT: This paper proposes a new image-based visual servoing scheme for stabilizing the nonholonomic mobile robot equipped with a monocular vision system to the desired configuration. In the vision system, neither intrinsic nor extrinsic camera parameters are calibrated. In addition, the lack of depth information should be tackled when using a monocular camera. The main difficulty encountered lies in the simultaneous existence of nonholonomic constraints, uncalibrated camera parameters and unknown depth. To deal with these problems, a dual-loop control structure is utilized. For the inner loop, an extended state observer is constructed to observe the system uncertainties caused by the uncalibrated camera parameters and unknown depth. For the outer loop, a switching controller is synthesized based on the compensated system model to maneuver the mobile robot to the desired configuration. Simulations and experimental results illustrate the effectiveness and robustness of the proposed control scheme. GRAPHICAL ABSTRACT: